2021
DOI: 10.1002/chem.202005147
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of 1H Paramagnetic Chemical Shifts in Actinide Complexes, Beyond Bleaney's Theory: The AnVIO22+–Dipicolinic Acid Complexes (An=Np, Pu) as an Example

Abstract: with dipicolinic acid derivatives were synthesized and characterized by powder XRD, SQUID magnetometrya nd NMR spectroscopy.I na ddition, Np VI and Pu VI complexes were described by first principles CAS based and two-component spin-restricted DFT methods. The analysis of the 1 Hp aramagnetic NMR chemical shifts for all protons of the ligands according to the X-rays structures shows that the Fermi contact contribution is negligible in agreement with spin density determined by unrestrictedDFT.The magnetic suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 85 publications
2
35
0
Order By: Relevance
“…The δ FCS contribution, as expressed in eqs S2–S5 and refs and , depends on the spin contribution to the magnetic susceptibility χ S from the paramagnetic center and, on the spin density at the NMR active nucleus K ρ S ( r K ). A full theoretical determination of δ FCS was, unfortunately, not possible due to the difficulty in computing the term K ρ S ( r K ).…”
Section: Resultsmentioning
confidence: 99%
“…The δ FCS contribution, as expressed in eqs S2–S5 and refs and , depends on the spin contribution to the magnetic susceptibility χ S from the paramagnetic center and, on the spin density at the NMR active nucleus K ρ S ( r K ). A full theoretical determination of δ FCS was, unfortunately, not possible due to the difficulty in computing the term K ρ S ( r K ).…”
Section: Resultsmentioning
confidence: 99%
“…The computational approach focuses then on the ab initio evaluation of the anisotropy of the χ tensor. This allows the full description of the paramagnetic center with all excited states, either partially populated or not, and strongly magnetically coupled . We will follow this approach in this work.…”
Section: Introductionmentioning
confidence: 97%
“…21 It has early been shown that a T −3 correction term can be necessary 22 and this was recently successfully applied in the [Ln III (DPA)3] 3-, [An III (DPA)3] 3and [An VI O2(DPA)2] 2-. 11,23 The computation from first principles of pNMR shifts requires a balanced description of the multiconfigurational electronic structure of the paramagnetic center in order to describe its magnetic susceptibility, and, of the metal-ligand spin delocalization and polarization for the contact contribution. Many computational approaches to calculate pNMR shieldings are based on Kurland-McGarvey theory.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations